Use of evidence-based health professions education: Attitudes and practices of academic leaders. - Shazia Nawabi; Rida Fatima Waseem; AbdulAziz Binrayes; Ayman Moaz Abulhamael; Zaina Ahmad; Kiran Imtiaz Khan; Syed Rashid Habib; Muhammad Qasim Javed (PLoS ONE)
Purpose The objective of this study was to explore the attitudes, practices, supports, and barriers of academic leaders regarding the use of Evidence-Based Health Professional Education (EBHPE). Methods A cross-sectional survey was conducted on 79 faculty members in leadership positions, from four different undergraduate colleges at Qassim University. A pre-validated questionnaire was distributed electronically. The e-questionnaire was comprised of 38 questions regarding participants' demographics, attitudes, practices, and perceived barriers/supports towards EBHPE. Data was analyzed using SPSS. Descriptive statistics were calculated for demographic characteristics and responses to survey items. The frequency distribution of the subjects was analyzed, and the median and means were calculated. Kruskall-Wallis and Mann-Whitney U tests were used for comparison of the means between the demographic groups. Spearman correlation was utilized to determine any relationships between the questionnaire's three sections. Results Of the 79 participants, 24 were Department Heads and 48 were female. The mean±SD values for Attitude, Practices and Support/Barriers were found to be 3.47±0.40, 2.72±0.84 and 3.34±0.43, respectively. The mean value of Attitude Score was > 3.41, therefore, it was interpreted that respondents had positive attitude towards EBHPE. Conversely, the values for Practices and Support/Barriers were interpreted as neutral (range = 2.61-3.40), neither good nor bad. The correlation coefficients between 'attitudes' and 'supports and barriers' (0.388) and 'practices' and 'supports and barriers' (0.388) indicated the weak association between these factors. The Cronbach's α value for questionnaire was found to be 0.887 indicating its reliability. Conclusions This study concludes that the respondents had positive attitude towards EBHPE. However, this positive attitude was not reflected in their practices. Healthcare professionals should be committed to educational excellence, and endeavour to rely on evidence-based literature regarding the planning and review of learning, teaching, and assessment strategies.